CONSERVING MODERATE ISLAM IN INDONESIA: An Analysis of Muwafiq's Speech on Online Media (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
This study aimed to examine the ideas of one prominent Nahdlatul Ulama (NU) preacher named KH Ahmad Muwafiq (Muwafiq) about Islamic moderation in Indonesia while preaching in Bogor Palace on November 21, 2018. Through content analysis of Muwafiq’s preaching that was uploaded on YouTube media, this study found that there are two main themes in Muwafiq’ speech that were seemed related to the efforts to conserve moderate Islam; first is his preaching model has emulated the Prophet Muhammad model in proselytising Islam, such as wise, non-violent, and adjustable to the character and condition of the society. The second is related to the influence of tradition and culture in the implementation of Islamic teachings.